Cell-derived vesicles for delivery of cancer immunotherapy - Jialu Xu; Chao Wang (Open Exploration Publishing Inc., 2021)
In recent years, cancer immunotherapy has received unprecedented attention due to the clinical achievements. The applications of biomedical engineering and materials science to cancer immunotherapy have solved the challenges caused by immunotherapy to a certain extent. Among them, cell-derived vesicles are natural biomaterials chosen as carriers or immune-engineering in view of their many unique advantages. This review will briefly introduce the recent applications of cell-derived vesicles for cancer immunotherapy.